New nomenclature notes and typification in Luehea and Lueheopsis (Malvaceae: Grewioideae) - Gerace, Samuele; Bovini, Massimo G.; A. Baumgratz, José Fernando (Phytotaxa, 2024)
This review examines the names and type specimens for the genera Luehea and Lueheopsis. We have analyzed 10 Lueheopsis, and 20 Luehea names, and designated two neotypes and sixteen lectotypes.